Impact of Cesium/Rubidium Incorporation on the Photophysics of Multiple‐Cation Lead Halide Perovskites. Issue 6 (17th April 2020) - Gao, Yajun; Wang, Kai; Wang, Mingcong; Khan, Jafar I.; Balawi, Ahmed H.; Liu, Wenzhu; De Wolf, Stefaan; Laquai, Frédéric
Abstract : Incorporating cesium (Cs) or rubidium (Rb) cations into multiple‐cation lead mixed halide perovskites (FA0.83 MA0.17 Pb(I0.83 Br0.17 )3 ) increases their photovoltaic performance. Herein, the fundamental photophysics of perovskites are investigated by steady‐state and transient optical spectroscopy and the reasons for the performance increase are revealed. Cs/Rb‐cation incorporation slightly increases the bandgap, whereas exciton binding energies remain in the range of a few meV. Urbach energies are reduced, suggesting improved perovskite microstructure upon Cs/Rb incorporation. Carrier density‐induced broadening of the photo‐bleaching following the Burstein–Moss model is observed, and the effective carrier masses are determined to be a few tenths of the electron rest mass. From fits of the high‐energy tail of the perovskite's photo bleach to Boltzmann's distribution, subpicosecond hot‐carrier cooling is revealed, implying strong carrier–phonon coupling. Importantly, the charge carrier recombination dynamics indicate that Cs/Rb‐incorporation reduces both the first‐order (trap‐assisted) and the second‐order (radiative) recombination, which appears to be the main reason for the observed performance increase upon Cs/Rb‐cation incorporation. Overall, this work presents a detailed study of the photophysics of multiple‐cation mixed halide lead perovskites and develops a concise picture of the impact of cesium/rubidium incorporation on the photophysics and device performance. Abstract : The partial substitution of methylammonium (MA) and formamidinium (FA) cations by cesium (Cs) or rubidium (Rb) cations in multiple‐cation lead mixed halide perovskites, (FA0.83 MA0.17 Pb(I0.83 Br0.17 )3 ), reduces the trap‐assisted (k1 ) and radiative (k2 ) charge carrier recombination rate. Furthermore, Urbach energies are reduced, indicating improved perovskite film microstructure. Consequently, photovoltaic devices with Cs/Rb‐incorporated perovskites exhibit improved power conversion efficiency.